2019
DOI: 10.1089/chi.2018.0083
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition-Related Practices of Family Child Care Providers and Differences by Ethnicity

Abstract: Background: Child care settings play an important role in shaping children's eating behaviors; yet few studies have included family child care homes (FCCHs). We examined provider-reported nutrition-related practices in FCCHs and observed adherence to nutrition guidelines from the Nutrition and Physical Activity Self-Assessment for Child Care (NAP SACC), exploring differences by provider ethnicity. Methods: We assessed baseline data from a cluster-randomized trial, including surveys with FCCH providers and obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 68 publications
(101 reference statements)
4
21
3
Order By: Relevance
“…When comparing observational versus self-report studies, researchers emphasise that all child feeding practices are unlikely to occur within one mealtime, therefore several time points should be studied to accommodate variations in feeding practices across the day or week [13]. Desirable feeding practices are also more likely to be recorded in self-report studies due to social desirability bias [55]. In our study, participants perceived their limited observation of desirable child feeding practices within the childcare setting to be the result of parental influence, established childcare procedures and training of centre staff.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When comparing observational versus self-report studies, researchers emphasise that all child feeding practices are unlikely to occur within one mealtime, therefore several time points should be studied to accommodate variations in feeding practices across the day or week [13]. Desirable feeding practices are also more likely to be recorded in self-report studies due to social desirability bias [55]. In our study, participants perceived their limited observation of desirable child feeding practices within the childcare setting to be the result of parental influence, established childcare procedures and training of centre staff.…”
Section: Discussionmentioning
confidence: 99%
“…Sisson et al (2017) [46] reported that communicating with parents is essential for childcare educator motivation; that educators feel discouraged if their healthy eating efforts are unsupported within the home environment. Working with childcare educators to increase their efficacy in having mutually respectful, constructive conversations with families about potentially sensitive feeding issues is therefore an important consideration if learnt knowledge is expected to translate into practice [24,46,55,62].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations